Agronomic performance of canola at different row spacing and plant densities - Bandeira, Taiane Pettenon; Chavarria, Geraldo; Tomm, Gilberto Omar (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the agronomic performance of canola at different row spacing and plant densities. A randomized complete block design was used with four replicates in a split plot arrangement. The plots consisted of row spacing (17, 34, 51 and 68 cm), and subplots consisted of plant densities (15, 30, 45 and 60 plants per square meter). The experiments were carried out in 2011 and 2012. Evaluations were done for: number of secondary, tertiary, and quaternary branches; number of pods on primary, secondary, tertiary, and quaternary branches; number of pods per plant; number of grains per plant; thousand grain weight; grain yield; apparent biological yield per plant; straw and grain yield per plant; and harvest index. The largest numbers of branches, pods per plant, and grains per plant, as well as the highest total mass of plants were obtained when using plant density of 15 plants per square meter. The highest grain yield per area is obtained when using 17 cm row spacing and plant density of 45 plants per square meter.